Mulching modifies coriander yield (Research, Society and Development, 2021)
In the Brazilian semiarid region, water is a restrictive aspect both for family and animal consumption, and for growing food. Covering the soil with vegetable debris can reduce the evaporation of water made available to plants. In view of the above, the objective of the work was to determine a mulch of soil that meets the requirements of the culture of coriander (Coriandrum sativum) and improves the productive performance of this apiaceae. The treatments consisted of four dead coverings, using the species: Leucena (Leucaena leucocephala), Neem (Azadirachta indica), Silk-flower (Calotropis procera), Carnaúba (Copernicia prunifera), and a witness (without dead cover). The influence of coverages on coriander at 10, 20 and 30 days after sowing was analyzed. The different types of soil cover, associated with the evaluation periods, changed the behavior of the coriander culture. It is recommended to cover coriander the use of Leucena straw) for high yields. Other works involving the theme of mulch for the semiarid region must be developed, to better use the hydrological resource of this region, given its scarcity. Perspectives such as other species for mulch, cover density and straw decomposition level are attributes that can be analyzed and added to this study.